Properties of extracted Eucalyptus globulus kraft pulps - Duarte, G. V. (2012)
This work was a comprehensive study of the properties of extracted Eucalyptus globulus kraft pulps. Five levels of hot water extraction were performed, each followed by kraft cooking to three different kappa numbers. As extraction took place, the hemicelluloses content of the kraft pulps was reduced from 21%-22% to 3%-4% and, conversely, the cellulose fraction increased from 73%-75% to 85%-90%. Fiber length decreased for all pulps and kink index increased greatly with extraction. The dispersive components of the surface energy for the control (unextracted) and extracted (120 min) kappa no. 15 kraft pulps, as determined by inverse gas chromatography, were found to be 30.8 and 34.9 mJ/m2, respectively. The acid-base properties of the pulp surface seemed to be enhanced by the inclusion of the hot-water extraction step. We discuss the surface energy properties in terms of the chemical structure of the pulps. In addition, we report on two models able to predict the mass removal and kappa number of pulps prepared from preextracted chips. Application: This work can give mills an understanding of the effect of hot water extraction on the properties of E. globulus kraft pulps.